Frecuencia de la pérdida prematura de primeros molares definitivos en niños de 7 a 9 años que acuden a la Clínica Odontológica de la Universidad de las Américas en el período septiembre – octubre 2017 - Dávila León, Gabriel Antonio (2018)
The first definitive molar since its eruption has a very important role in the oral cavity, since this piece is a guide for dental replacement and occlusion. The first definitive molars erupt at approximately 6 years of age. The loss of this piece will produce remarkable changes in the oral cavity. Objective: To determine the behavior of the early loss of the first definitive molar in 7- to 9-year-old children who comes to be attend in the dental clinic of the University of the Americas in the period of September to October 2017. Materials and methods: This study was realized from a sample of 70 patients who was attended in the Odontology Clinic of the University of the Americas in the period from September to October 2017, with ages ranging from 7 to 9 years. The information was collected in the Integral Clinic of the University of the Americas by the researcher. To determine the loss of the first definitive molar, patients were examined with the help of an oral mirror; this information was collected in a data collection form. Results: The patients who presented a loss of the first definitive molar were the children of 7 years of age with 50%, followed by the children of 9 years with 31.4% and finally the years of 8 years with 18.6%. The gender that predominated was male with 51.4%. Conclusion: It was evidenced that due to the lack of knowledge of the representatives of the patients about the first definitive molar, they ordered the extraction of the piece thinking it was a deciduous molar.